2017
DOI: 10.1038/nchembio.2463
|View full text |Cite
|
Sign up to set email alerts
|

Probing the roles of SUMOylation in cancer cell biology by using a selective SAE inhibitor

Abstract: Small ubiquitin-like modifier (SUMO) family proteins regulate target-protein functions by post-translational modification. However, a potent and selective inhibitor targeting the SUMO pathway has been lacking. Here we describe ML-792, a mechanism-based SUMO-activating enzyme (SAE) inhibitor with nanomolar potency in cellular assays. ML-792 selectively blocks SAE enzyme activity and total SUMOylation, thus decreasing cancer cell proliferation. Moreover, we found that induction of the MYC oncogene increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
177
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(198 citation statements)
references
References 49 publications
20
177
1
Order By: Relevance
“…In support of this, UBC9 depletion exacerbated the adverse effect of 5‐azadC on cell proliferation (Fig C). Moreover, acute inhibition of SUMOylation by treatment with ML‐792 (SUMO‐E1i), a recently described small molecule inhibitor of the SUMO E1 enzyme SAE (He et al , ), abolished 5‐azadC‐induced chromatin SUMOylation and strongly impaired the timely clearance of endogenous DNMT1 DPCs (Fig D and E). Unlike suppression of SUMOylation, SPRTN depletion only modestly compromised cell proliferation and GFP‐DNMT1 DPC clearance following 5‐azadC treatment while knockdown of ZNF451, a SUMO E3 ligase recently implicated in resolving TOP2 DPCs (Schellenberg et al , ), had no effect (Figs F, and EV2D and E), suggesting that SUMO‐dependent modification and processing of DNMT1 DPCs can proceed via other enzymatic activities.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In support of this, UBC9 depletion exacerbated the adverse effect of 5‐azadC on cell proliferation (Fig C). Moreover, acute inhibition of SUMOylation by treatment with ML‐792 (SUMO‐E1i), a recently described small molecule inhibitor of the SUMO E1 enzyme SAE (He et al , ), abolished 5‐azadC‐induced chromatin SUMOylation and strongly impaired the timely clearance of endogenous DNMT1 DPCs (Fig D and E). Unlike suppression of SUMOylation, SPRTN depletion only modestly compromised cell proliferation and GFP‐DNMT1 DPC clearance following 5‐azadC treatment while knockdown of ZNF451, a SUMO E3 ligase recently implicated in resolving TOP2 DPCs (Schellenberg et al , ), had no effect (Figs F, and EV2D and E), suggesting that SUMO‐dependent modification and processing of DNMT1 DPCs can proceed via other enzymatic activities.…”
Section: Resultsmentioning
confidence: 84%
“…The EMBO Journal 38: e101496 | 2019 recently described small molecule inhibitor of the SUMO E1 enzyme SAE(He et al, 2017), abolished 5-azadC-induced chromatin SUMOylation and strongly impaired the timely clearance of endogenous DNMT1 DPCs(Fig 3D and E). Unlike suppression of SUMOylation, SPRTN depletion only modestly compromised cell proliferation and GFP-DNMT1 DPC clearance following 5-azadC treatment while knockdown of ZNF451, a SUMO E3 ligase recently implicated in resolving TOP2 DPCs…”
mentioning
confidence: 94%
“…We then intended to establish a role of SUMOylation in TOP-DPC processing. Utilizing ML-792, an inhibitor of the SUMO-activating enzyme SAE (He et al, 2017), we found that inhibiting SUMOylation blocked drug-induced loss of TOPs (Figure 2A, B, lanes 7) while increasing TOP-DPCs ( Figure S2C-H). Using an antibody that selectively recognizes TOP1-DPCs (Patel et al, 2016), immunofluorescence (IF) microscopy showed that inhibition of the proteasome, ubiquitylation or SUMOylation increased TOP1-DPCs ( Figure 2I, J), corroborating the involvement of SUMOylation, ubiquitylation and proteasome in TOP1-DPC resolution.…”
Section: Sumo- Ub-and Proteasome-dependent Processing Of Top-dpcs Inmentioning
confidence: 97%
“…The important SUMO-based regulatory events exemplified above could explain the drastic chromosome segregation defects arising from acute chemical inhibition of SUMO E1 or depletion of SUMO E2 and specific desumoylases (He et al, 2017; Mukhopadhyay and Dasso, 2017; Nacerddine et al, 2005; Pelisch et al, 2014). Strikingly, aneuploidy-prone SUMO pathway mutants may produce adaptive situations wherein gaining an extra chromosome partially resets cellular homeostasis, as seen in yeast cells lacking the Ulp2 desumoylase (Ryu et al, 2016).…”
Section: Sumo Modulates Chromosome Structures and Functionsmentioning
confidence: 99%